Investigating the Influence of Work Safety Scale (WSS) on Safety Behaviour: A Study among Employees of a Utility Company - Maithily, Karuppiah (2011)
This study is to determine the influence of the five facets of Work Safety Scale (WSS) on compliance with safety behaviour among the employees of a utility company in Malaysia. The study was held as there were only limited studies on safety being carried out in utility industry. Trainings and awareness programs had been aggressively put into actions to get the staffs involvement and commitment over safety; yet there are still incidents and accidents occurring on safety issues. In addition, this study also investigates how the safety perception measurement contributes to the safety behavior among the employees in utility industry. A total of 110 questionnaires had been distributed to the sample chosen on the study consisting of five independent variables of Work Safety Scale that are: (a) job safety, (b) co-worker safety, (c) supervisor safety, (d) management safety practices and (e) satisfaction of the safety programme. All those independent variables later will be measured on the perception of workplace safety towards the compliance of safety behaviour as the determinants (dependent variable). Finally, the finding of the study presented that co-worker safety, supervisor safety, management safety practices and safety programmes are significantly related to compliance safety behaviour whilst job safety have no any intercorrelation to safety behaviour in the study.